(3GdGSJjYGH aj eYQaI GdCUMGHs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3HGH YeQ YeQ Hf GdNWGH Hf fajd s
(3BNQgG (B:s
(3Ydi Hf GdMce GdSdei , CNh eYGhjI Hf GdMce s
(3bWYI efJRYI ef GdSaQ GdKGdKs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHI GdbGVi CMeO Hf Ydi GdCchY GdNGUI s
Keywords: (3GdJGQjNs